Two-spotted spider mite and its natural enemies on strawberry grown as protected and unprotected crops in Norway and Brazil - Castilho, Raphael C. [UNESP]; Duarte, Vanessa S.; Moraes, Gilberto J. de; Westrum, Karin; Trandem, Nina; Rocha, Luiz Carlos D.; Delalibera, Italo; Klingen, Ingeborg (Springer, 2015)
Cultivation of strawberry in plastic tunnels has increased considerably in Norway and in southeastern Brazil, mainly in an attempt to protect the crop from unsuitable climatic factors and some diseases as well as to allow growers to expand the traditional production season. It has been hypothesized that cultivation under tunnels could increase the incidence of one of its major pests in many countries where strawberry is cultivated, including Norway and Brazil, the two spotted spider mite, Tetranychus urticae. The objective of this study was to evaluate the effect of the use of tunnels on the incidence of T. urticae and on its natural enemies on strawberry in two ecologically contrasting regions, Norway (temperate) and southeastern Brazil (subtropical). In both countries, peak densities of T. urticae in tunnels and in the open fields were lower than economic thresholds reported in the literature. Factors determining that systematically seem to be the prevailing relatively low temperature in Norway and high relative humidity in both countries. The levels of occurrence in Norway and Brazil in 2010 were so low that regardless of any potential effect of the use of tunnel, no major differences were observed between the two cropping systems in relation to T. urticae densities. In 2009 in Norway and in 2011 in Brazil, increase in T. urticae population seemed to have been restrained mainly by rainfall in the open field and by predatory mites in the tunnels. Phytoseiids were the most numerous predatory mite group of natural occurrence on strawberry, and the prevalence was higher in Brazil, where the most abundant species on strawberry leaves were Neoseiulus anonymus and Phytoseiulus macropilis. In Norway, the most abundant naturally occurring phytoseiids on strawberry leaves were Typhlodromus (Anthoseius) rhenanus and Typhlodromus (Typhlodromus) pyri. Predatory mites were very rare in the litter samples collected in Norway. Infection rate of the pest by the fungus Neozygites floridana (Neozygitaceae) was low. The results of this work suggest that in Norway the use of tunnels might not affect the population densities of T. urticae on strawberry in years of lower temperatures. When temperature is not a limiting factor for the development of T. urticae in that country (apparently always the case in southern Brazil), strawberry cultivation in the tunnels may allow T. urticae to reach higher population levels than in open fields (because of the provided protection from the direct impact of rainfall), but natural enemies may prevent higher levels from being reached.
Keywords: Tetranychus urticae; Predatory mites; Neozygites floridana; Diversity